Women in management, champions of change : papers presented at the Third Academic Conference of Management Development Institutions in South Asia (AMDISA) : February 7, 1994 Dhaka, Bangladesh - Association of Management Development Institutions in South Asia. Academic Conference 1994 : Dhaka, Bangladesh); Sogra, Khair Jahan (Dhaka : University Press, 1994)
With special reference to South Asia.
Includes bibliographical references.
Keywords: Women executives -- South Asia -- Congresses; Businesswomen -- South Asia -- Congresses